Radial acceleration and cumulation of ions by an intense converging ring laser pulse - Balakirev, V.A.; Onishchenko, I.N.; Povrozin, A.I.; Tolstoluzhsky, A.P.; Yegorov, A.M. (Вопросы атомной науки и техники, 2008)
Cumulation dynamics and acceleration of deuterium plasma ions by a focused ring laser pulse of the femtosecond duration are theoretically investigated. Laser pulse is focused by a dielectric lens. The spatial structure of ring laser pulse field in the vicinity of the lens focus is determined. The values of cumulation coefficient of ions, their energy, and cumulation region dimensions are obtained. Conclusions are made about the possibility of the neutron source elaboration on considered cumulation principle. Досліджена динаміка кумуляції і прискорення іонів дейтерієвої плазми сфокусованим кільцевим лазерним імпульсом фемтосекундної тривалості. Визначена просторова структура поля кільцевого лазерного імпульсу поблизу фокуса лінзи. Отримані значення коефіцієнта кумуляції іонів, їх енергії та розміри області кумуляції. Зроблені висновки відносно можливості розробки нейтронного джерела на принципі кумуляції, що розглядається. Исследована динамика кумуляции и ускорения ионов дейтериевой плазмы сфокусированным кольцевым лазерным импульсом фемтосекундной длительности. Определена пространственная структура поля кольцевого лазерного импульса в окрестности фокуса линзы. Получены значения коэффициента кумуляции ионов, их энергии и размеры области кумуляции. Сделаны выводы относительно возможности разработки нейтронного источника, основанного на рассматриваемом принципе кумуляции.